X-RAY DIFFRACTION PHASE ANALYSES FOR GRANULATED AND SINTERED CERAMIC MATERIALS - Pratapa, Suminar (UI Scholars Hub, 2007)
One basic problematic aspect in x-ray diffraction phase analysis is microabsorption effect which may arise from the size of the crystallite phases. Complication of the problem may intensify in sintered ceramic materials where milling of the samples is not simple. We report the Rietveld x-ray diffraction phase analysis of MgO-a-Al2O3 powder mixtures with phase content ratio of 1:1 by weight and MgO-Y2O3 sintered ceramic composites with Y2O3 contents of 10%, 20% and 30% by weight. The mixtures were pre-sintered at 1000°C for 2 hours and then milled while the composites were sintered at 1550°C for 3 hours. The phase composition analysis was done using Rietica, a non-commercial Rietveld method-based software. Relative and absolute phase compositions were examined and results showed that there was a significant amount of phase composition bias resulted from the examination. For the powder mixture, milling can reduce microabsorption effect and hence the calculation bias. For the ceramic composite where milling is almost impossible, additional of Y2O3 caused smaller crystallite size of MgO, so that composition bias is smaller in composites with higher Y2O3 content. A mathematical model is proposed to provide more acceptable phase composition results.